2018
DOI: 10.1080/2162402x.2018.1424671
|View full text |Cite
|
Sign up to set email alerts
|

Low dose gemcitabine increases the cytotoxicity of human Vγ9Vδ2 T cells in bladder cancer cellsin vitroand in an orthotopic xenograft model

Abstract: Human γδT cell immunotherapy is well tolerated and has shown promising results in clinical trials; however, its antitumor efficacy is limited, including results in solid tumors. expanded γδT cell stimulated by zoledronic acid (ZOL) activates the γδT cell subpopulation of so called Vγ9Vδ2 T cells. To improve the clinical outcomes of Vγ9Vδ2 T cell (abbreviated as γδT cell here) immunotherapy, we aimed to increase the cytotoxicity of γδT cells by focusing on two issues: recognition of tumor cells by γδT cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The Phase II study NCT03519256, enrolling subjects with high-risk, non-MIBC, is monitoring the therapeutic profile of BMS-986205 combined with two drugs already approved for some types of bladder cancer such as nivolumab [200][201][202][203][204] and the toll like receptor 2 (TLR2)/TLR4 agonist [205][206][207][208][209] bacillus Calmette-Guérin (BCG). [210][211][212] Along similar lines, the Phase III study NCT03661320 compared the efficacy, tolerability and safety of three therapeutic regimens for MIBC: neoadjuvant standard of care chemotherapy with cisplatin [213][214][215][216][217] and gemcitabine, 218,219 (NAC) versus NAC combined with nivolumab or nivolumab plus BMS-986205, followed by continuation of adjuvant immunotherapy (nivolumab with or without the IDO1 inhibitor) post radical cystectomy. 220 Additionally, four ongoing studies aim at elucidating the therapeutic profile of BMS-986205 in combination with nivolumab in patients affected by endometrial carcinoma or endometrial carcinosarcoma (NCT04106414), unresectable or metastatic HCC (NCT03695250), stage II to IV HNSCC (NCT03854032), as well as stage III or IV melanoma (NCT04007588).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Phase II study NCT03519256, enrolling subjects with high-risk, non-MIBC, is monitoring the therapeutic profile of BMS-986205 combined with two drugs already approved for some types of bladder cancer such as nivolumab [200][201][202][203][204] and the toll like receptor 2 (TLR2)/TLR4 agonist [205][206][207][208][209] bacillus Calmette-Guérin (BCG). [210][211][212] Along similar lines, the Phase III study NCT03661320 compared the efficacy, tolerability and safety of three therapeutic regimens for MIBC: neoadjuvant standard of care chemotherapy with cisplatin [213][214][215][216][217] and gemcitabine, 218,219 (NAC) versus NAC combined with nivolumab or nivolumab plus BMS-986205, followed by continuation of adjuvant immunotherapy (nivolumab with or without the IDO1 inhibitor) post radical cystectomy. 220 Additionally, four ongoing studies aim at elucidating the therapeutic profile of BMS-986205 in combination with nivolumab in patients affected by endometrial carcinoma or endometrial carcinosarcoma (NCT04106414), unresectable or metastatic HCC (NCT03695250), stage II to IV HNSCC (NCT03854032), as well as stage III or IV melanoma (NCT04007588).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…The Phase II study NCT03519256, enrolling subjects with high-risk, non-MIBC, is monitoring the therapeutic profile of BMS-986205 combined with two drugs already approved for some types of bladder cancer such as nivolumab 200 - 204 and the toll like receptor 2 (TLR2)/TLR4 agonist 205 - 209 bacillus Calmette–Guérin (BCG). 210 212 Along similar lines, the Phase III study NCT03661320 compared the efficacy, tolerability and safety of three therapeutic regimens for MIBC: neoadjuvant standard of care chemotherapy with cisplatin 213 - 217 and gemcitabine, 218 , 219 (NAC) versus NAC combined with nivolumab or nivolumab plus BMS-986205, followed by continuation of adjuvant immunotherapy (nivolumab with or without the IDO1 inhibitor) post radical cystectomy. 220 …”
Section: Translational and Clinical Progressmentioning
confidence: 99%
“…In this study, the authors used an ectopic model of subcutaneous cancer cell engraftment; however, orthotopic models of urinary bladder or renal pelvis might be preferable, as they better reflect the natural behavior of UC cells. This could be accomplished by transurethral administration of UC cancer cells, as we reported previously . As the results of this strategy showed that a combination of immunomodulatory agents and ICIs can yield successful results, various immunomodulatory agents have been investigated.…”
mentioning
confidence: 97%
“…We previously reported the appropriate orthotopic animal model of urinary bladder cancer, and investigated the efficacy and safety of intravesical cdT cells. 6 In that study, the UMUC3 cell line was transfected with the luciferase gene (Table S1). Luciferase signal-expressing UMUC3 cancer cells (UMUC3-luc) were established accordingly and used in the experiments shown below.…”
mentioning
confidence: 99%
“…We previously reported the appropriate orthotopic animal model of urinary bladder cancer, and investigated the efficacy and safety of intravesical γδT cells . In that study, the UMUC3 cell line was transfected with the luciferase gene (Table S1).…”
mentioning
confidence: 99%